Method for preparing residual oil hydrocracking catalyst by coupling ball milling method with Joule heat pulse
Through the combination of ball grinding method and coke ear thermal pulse method, prepare a hydrogenation catalyst with high activity and small particle size, solve the problem of uneven distribution of metal activity components in the existing catalyst, and achieve efficient plus efficient plus increase Hydrogen desulfurization and hydrogenation effect.
Patent Information
- Application Number
- CN202411570494.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
The metal active components of existing hydrogenation catalysts are unevenly distributed, resulting in insufficient catalytic activity.
Coupling the scorching ear thermal pulse method of the ball milling method is used to prepare the residue oil hydrogenation catalyst, and the uniform mixing and close contact of the metal active component is realized through the ball milling method. Catalyst.
The activity of the catalyst is improved, the effect of hydrogenation desulfurization and hydrogenation experiments, and shortening the baking time of the catalyst, saving energy.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a method for preparing a residual oil hydrocracking catalyst by coupling a ball milling method with a Joule heat pulse. Background Art
[0002] Refineries perform hydroprocessing to remove sulfur (hydrodesulfurization HDS) and nitrogen (hydrodenitrogenation HDN) from heterocyclic compounds. In addition to desulfurization and denitrogenation, the hydroprocessing process also requires hydrogenation (HYD) of some aromatic compounds in petroleum. The active component of industrial hydroprocessing catalysts is mainly cobalt or nickel-doped molybdenum disulfide (MoS2). The preparation method of this type of catalyst is usually an impregnation method, that is, molybdenum, cobalt, and nickel compounds are impregnated sequentially or simultaneously onto an alumina carrier, and then calcined to obtain a supported metal oxide. The metal oxide is then converted into the real active component, namely the Co-Mo-S phase or the Ni-Mo-S phase, through sulfurization activation.
[0003] CN95107484A provides a method for preparing a hydrogenation catalyst, wherein a molybdenum-containing carrier having a MoO3 content of 6 to 13 wt% is first prepared by an impregnation method or a kneading method, and then impregnated with an ammonia solution of a Ni-Mo mixture, and then calcined and reduced. The obtained catalyst has a high catalytic hydrogenation activity. However, in this method, after obtaining the molybdenum-containing carrier, the catalyst is impregnated with an ammonia solution of a Ni-Mo mixture, and the distribution effect of the metal on the catalyst is not good.
[0004] CN117757512A discloses a method for hydrogenating residual oil. Example 1 in the specification discloses: Weigh 1000.0g of aluminum oxide dry rubber powder, add 20.0g of citric acid and 20.0g of sesbania powder, mix well, add 1000.0g of aqueous solution containing 1.0% nitric acid, roll for 20.0min, and extrude strips with a clover plate with a diameter of 1.8mm. After drying at 120℃ for 6.0h, roast at 700℃ for 6.0h. The carrier after roasting is recorded as S-1 (After analysis, the pore properties of the carrier are as follows: the specific surface area of the carrier is 270m 2 / g, the carrier pore volume is 0.9cm 3 / g). Weigh 74.2g of ammonium heptamolybdate tetrahydrate, 47.3g of nickel nitrate hexahydrate, and 150.0g of deionized water. Stir thoroughly for 20min at 60°C, cool to room temperature, and then make up to 200.0mL with deionized water. The resulting solution is recorded as Q-1. Take 200g of carrier S-1, impregnate it with Q-1, dry it naturally for 24 hours, then dry it at 120°C for 4 hours, and then calcine it at 450°C for 5.0 hours. The oxidized catalyst obtained is recorded as CT-1 (based on the weight of the catalyst, the content of the carrier is 73.3%, the content of molybdenum as oxide is 22.2%, and the content of nickel as oxide is 4.5%). The metal active components of this method are also loaded on the carrier by impregnation, and the distribution effect needs to be improved.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse.
[0007] The basic concept of the technical solution of the present invention is as follows: The method for preparing a residue oil hydrocracking catalyst by ball milling coupled with Joule heat pulse comprises the following steps: (1) Mixing a salt compound containing a metal element X with a salt compound containing Mo, a salt compound containing Al, and a molecular sieve to obtain a precursor material; the metal element X is at least one of Ni and Co; (2) adding the precursor material into a ball mill, adding a grinding solvent and grinding balls for ball milling to obtain a ground material; (3) drying the ground material and subjecting it to Joule heat pulse treatment to obtain catalyst powder; and then tableting, crushing and screening to obtain X-Mo / Al2O3 oxidation state catalyst particles; (4) immersing equal volumes of the X-Mo / Al2O3 oxidation state catalyst particles in an ammonium thiosulfate solution for presulfidation to obtain a presulfided catalyst; (5) Reducing the presulfided catalyst in a hydrogen atmosphere to obtain the residue hydrocracking catalyst in a sulfided state.
[0008] As one approach, the molar ratio of the X metal element, Mo, and Al is 1:(1-6):(3-30).
[0009] As one approach, in step (1), the mass proportion of the molecular sieve in the precursor material is (1-10)%.
[0010] As one method, the grinding solvent in step (2) is isopropanol; the volume ratio of isopropanol to the precursor material is (0.5~3):1.
[0011] As a method, in step (2), the diameters of the grinding balls are 20 mm, 10 mm and 5 mm respectively; the ball-to-material ratio is (3-5):1, the ball milling speed is (100-600) r / min, and the ball milling time is (6-12) h.
[0012] As a method, in step (3), the method of Joule heat pulse treatment is: replace the air in the sintering box with monatomic gas Ar, set the pulse conditions: the heating rate is (2000~4000)℃ / s, the number of pulses is (3~15) times, the upper limit temperature is (600~1000)℃, and the cooling time is ≤1.5s, down to 450℃±10℃.
[0013] As one approach, in step (4), the ratio of the molar amount of S to the total molar amount of the X metal element and Mo is (2-6):1.
[0014] Preferably, in step (4), the ratio of the molar amount of S to the total molar amount of the X metal element and Mo is 3:1.
[0015] As a method, in step (5), the hydrogen pressure is 20-40 bar and the heating rate is 1-5 o C / min, and at 200~350 o C is maintained for 30 to 120 minutes for reduction.
[0016] The present invention provides a residue hydrocracking catalyst, which is obtained by the method for preparing the residue hydrocracking catalyst by coupling the ball milling method with the Joule heat pulse according to any one of the above contents.
[0017] The present invention has the following advantages: 1. The present invention first prepares the catalyst precursor by ball milling. The ball milling process is simple, scalable, low-cost and environmentally friendly. At the same time, it can achieve uniform mixing and close contact of metal active components at the nanoscale, which is conducive to the formation of highly active Ni-Mo-S phase or Co-Mo-S phase during the sulfurization process.
[0018] Afterwards, the catalyst precursor is heat treated using the Joule heat pulse method. The pulse power supply controls the instantaneous temperature rise and fall of multiple cycles, and the instantaneous high temperature generated is used to promote the structural change of the catalyst precursor. In addition, rapid cooling inhibits grain growth, thereby preparing a residue oil hydrocracking catalyst with small particle size, high specific surface area and resistance to sintering.
[0019] 2. The method of the present invention does not adopt the common roasting process, which shortens the roasting time of the catalyst and is beneficial to saving energy.
[0020] 3. The present invention innovatively provides a catalyst preparation process using ball milling coupled with Joule heat pulse, filling the technical gap.
[0021] 4. The sulfided NiMo / Al2O3 or CoMo / Al2O3 catalyst prepared by the present invention has a high specific surface area. The results of hydrodesulfurization and hydrogenation experiments verify the high activity of the catalyst of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention is clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1 (1) Combine Ni(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and Al(NO3)3·9H2O are stirred and mixed evenly according to the molar ratio of metal elements Ni, Mo and Al of 1:3:20, and SAPO-34 molecular sieve (Si / (Si+Al+P)=0.05) is added while stirring to obtain a precursor material, in which the mass proportion of the molecular sieve in the precursor material is 5%.
[0024] (2) The precursor material obtained in step (1) was placed in a 125 ml corundum grinding jar (planetary ball mill PM100, Retsch), and isopropanol was added. The ratio of the volume of isopropanol to the volume of the precursor material was 1.5:1. At the same time, 5, 50, and 300 grinding balls with diameters of 20 mm, 10 mm, and 5 mm were placed in the grinding jar, respectively. The ball-to-material ratio was 4:1, the ball milling speed was 500 r / min, and the ball milling time was 8 h. After the ball milling was completed, the grinding balls were removed to obtain the ground material.
[0025] (3) Dry the ground material obtained in step (2) in an oven at 105°C for 12 hours to obtain a dry material. Take 5g of the dry material and place it in a carbon cloth, clamp it with copper sheets at both ends, and use a multimeter to measure the resistance at both ends of the carbon cloth. Replace the air in the sintering box with monatomic gas Ar, set the pulse conditions: the heating rate is 3000°C / s, the number of pulses is 5 times, the upper limit temperature is 800°C, the cooling time is 1.5s, and it drops to 450°C±10°C; after the pulse ends, the catalyst powder is obtained, and then pressed into tablets, crushed, and sieved, and 20-40 mesh NiMo / Al2O3 oxidation state catalyst particles are retained for use.
[0026] (4) impregnating an equal volume of the collected NiMo / Al2O3 oxidized catalyst into an ammonium thiosulfate solution, wherein the molar ratio of S to (Ni+Mo) is 3:1, and then drying at 105°C for 8 hours to obtain a presulfurized catalyst; (5) The presulfurized catalyst was placed in a 300 mL autoclave and heated at a hydrogen pressure of 30 bar and a heating rate of 3 o C / min, and at 300 o C is maintained for 60 min to carry out reduction to obtain a sulfided residue hydrocracking catalyst.
[0027] Example 2 (1) Combine Co(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and Al(NO3)3·9H2O are stirred and mixed evenly according to the molar ratio of metal elements Co, Mo and Al of 1:3:20, and a small amount of molecular sieve H-β molecular sieve (Si / Al=50) is added while stirring to obtain a precursor material, in which the mass proportion of the molecular sieve in the precursor material is 5%.
[0028] (2) The precursor material obtained in step (1) was placed in a 125 ml corundum grinding jar (planetary ball mill PM100, Retsch), and isopropanol was added. The ratio of the volume of isopropanol to the volume of the precursor material was 1.5:1. At the same time, 5, 50, and 300 grinding balls with diameters of 20 mm, 10 mm, and 5 mm were placed in the grinding jar, respectively. The ball-to-material ratio was 4:1, the ball milling speed was 500 r / min, and the ball milling time was 8 h. After the ball milling was completed, the grinding balls were removed to obtain the ground material.
[0029] (3) Dry the ground material obtained in step (2) in an oven at 105°C for 12 hours to obtain a dry material. Take 5g of the dry material and place it in a carbon cloth, clamp it with copper sheets at both ends, and use a multimeter to measure the resistance at both ends of the carbon cloth. Replace the air in the sintering box with monatomic gas Ar, set the pulse conditions: the heating rate is 3000°C / s, the number of pulses is 5 times, the upper limit temperature is 800°C, the cooling time is 1.5s, and it drops to 450°C±10°C; after the pulse ends, the catalyst powder is obtained, and then the catalyst is pressed into tablets, crushed, and sieved, and 20-40 mesh CoMo / Al2O3 oxidation state catalyst particles are retained for use.
[0030] (4) Immersing an equal volume of the collected CoMo / Al2O3 oxidized catalyst in an ammonium thiosulfate solution, wherein the molar ratio of S to (Co+Mo) is 3:1, and then drying at 105°C for 8 hours to obtain a presulfided catalyst; (5) The presulfurized catalyst was placed in a 300 mL autoclave and heated at a hydrogen pressure of 30 bar and a heating rate of 3 oC / min, and at 300 o C is maintained for 60 min to carry out reduction to obtain a sulfided residue hydrocracking catalyst.
[0031] Example 3 (1) Combine Ni(NO3)2·6H2O, (NH4)6Mo7O 24 ·4H2O and Al(NO3)3·9H2O were stirred and mixed evenly according to the molar ratio of metal elements Ni, Mo and Al of 1:6:20, and SAPO-34 molecular sieve (Si / (Si+Al+P)=0.05) was added while stirring to obtain a precursor material, in which the mass proportion of the molecular sieve in the precursor material was 5%.
[0032] (2) The precursor material obtained in step (1) was placed in a 125 ml corundum grinding jar (planetary ball mill PM100, Retsch), and isopropanol was added. The ratio of the volume of isopropanol to the volume of the precursor material was 1.5:1. At the same time, 5, 50, and 300 grinding balls with diameters of 20 mm, 10 mm, and 5 mm were placed in the grinding jar, respectively. The ball-to-material ratio was 4:1, the ball milling speed was 500 r / min, and the ball milling time was 8 h. After the ball milling was completed, the grinding balls were removed to obtain the ground material.
[0033] (3) Dry the ground material obtained in step (2) in an oven at 105°C for 12 hours to obtain a dry material. Take 5g of the dry material and place it in a carbon cloth, clamp it with copper sheets at both ends, and use a multimeter to measure the resistance at both ends of the carbon cloth. Replace the air in the sintering box with monatomic gas Ar, set the pulse conditions: the heating rate is 3000°C / s, the number of pulses is 10 times, the upper limit temperature is 1000°C, the cooling time is 1.5s, and it drops to 450°C±10°C; after the pulse ends, the catalyst powder is obtained, and then pressed into tablets, crushed, and sieved, and 20-40 mesh NiMo / Al2O3 oxidation state catalyst particles are retained for use.
[0034] (4) impregnating an equal volume of the collected NiMo / Al2O3 oxidized catalyst into an ammonium thiosulfate solution, wherein the molar ratio of S to (Ni+Mo) is 3:1, and then drying at 105°C for 8 hours to obtain a presulfurized catalyst; (5) The presulfurized catalyst was placed in a 300 mL autoclave and heated at a hydrogen pressure of 30 bar and a heating rate of 3 o C / min, and at 300 o C is maintained for 60 min to carry out reduction to obtain a sulfided residue hydrocracking catalyst.
[0035] Example 4 (1) Combine Co(NO3)2·6H2O, (NH4)6Mo7O 24·4H2O and Al(NO3)3·9H2O are stirred and mixed evenly according to the molar ratio of metal elements Co, Mo and Al of 1:6:20, and a small amount of molecular sieve H-β molecular sieve (Si / Al=50) is added while stirring to obtain a precursor material, in which the mass proportion of the molecular sieve in the precursor material is 5%.
[0036] (2) The precursor material obtained in step (1) was placed in a 125 ml corundum grinding jar (planetary ball mill PM100, Retsch), and isopropanol was added. The ratio of the volume of isopropanol to the volume of the precursor material was 1.5:1. At the same time, 5, 50, and 300 grinding balls with diameters of 20 mm, 10 mm, and 5 mm were placed in the grinding jar, respectively. The ball-to-material ratio was 4:1, the ball milling speed was 500 r / min, and the ball milling time was 8 h. After the ball milling was completed, the grinding balls were removed to obtain the ground material.
[0037] (3) Dry the ground material obtained in step (2) in an oven at 105°C for 12 hours to obtain a dry material. Take 5g of the dry material and place it in a carbon cloth, clamp it with copper sheets at both ends, and use a multimeter to measure the resistance at both ends of the carbon cloth. Replace the air in the sintering box with monatomic gas Ar, and set the pulse conditions: the heating rate is 3000°C / s, the number of pulses is 10 times, the upper limit temperature is 1000°C, the cooling time is 1.5s, and it drops to 450°C±10°C; after the pulse ends, the catalyst powder is obtained, and then the catalyst is pressed into tablets, crushed, and sieved, and 20-40 mesh CoMo / Al2O3 oxidation state catalyst particles are retained for use.
[0038] (4) Immersing an equal volume of the collected CoMo / Al2O3 oxidized catalyst in an ammonium thiosulfate solution, wherein the molar ratio of S to (Co+Mo) is 3:1, and then drying at 105°C for 8 hours to obtain a presulfided catalyst; (5) The presulfurized catalyst was placed in a 300 mL autoclave and heated at a hydrogen pressure of 30 bar and a heating rate of 3 o C / min, and at 300 o C is maintained for 60 min to carry out reduction to obtain a sulfided residue hydrocracking catalyst.
[0039] Comparative Example 1 (1) Stir 10 g Al2O3 and 0.5 g SAPO-34 molecular sieve (Si / (Si+Al+P)=0.05) thoroughly until well mixed.
[0040] (2) Use 30mL 0.15 mol / L (NH4)6Mo7O 24 The mixture obtained in step (1) was impregnated with 10 mL of 1 mol / L Ni(NO3)2 solution at room temperature for 1 h, and then dried in air.
[0041] (3) The ground material obtained in step (2) was dried in an oven at 105°C for 12 hours to obtain a dry material. Then, a tube furnace was used to bake the material at 450°C for 120 minutes under Ar gas atmosphere conditions with a gas flow rate of 200 mL / min and a heating rate of 5°C / min. The material was then pressed into tablets, crushed, and sieved to retain 20-40 mesh NiMo / Al2O3 oxidation state catalyst particles for later use.
[0042] (4) impregnating an equal volume of the collected NiMo / Al2O3 oxidized catalyst into an ammonium thiosulfate solution, wherein the molar ratio of S to (Ni+Mo) is 3:1, and then drying at 105°C for 8 hours to obtain a presulfurized catalyst; (5) The presulfurized catalyst was placed in a 300 mL autoclave and heated at a hydrogen pressure of 30 bar and a heating rate of 3 o C / min, and at 300 o C is maintained for 60 min to carry out reduction to obtain a sulfided residue hydrocracking catalyst.
[0043] Comparative Example 2 (1) Stir 10g Al2O3 and 0.5g H-β molecular sieve (Si / Al=50) thoroughly and mix well.
[0044] (2) Use 30mL 0.15 mol / L (NH4)6Mo7O 24 The mixture obtained in step (1) was impregnated with 10 mL of 1 mol / L Co(NO3)2 solution at room temperature for 1 h, and then dried in air.
[0045] (3) The ground material obtained in step (2) was dried in an oven at 105°C for 12 hours to obtain a dry material. Then, a tube furnace was used to bake the material at 450°C for 120 minutes under Ar gas atmosphere conditions with a gas flow rate of 200 mL / min and a heating rate of 5°C / min. The material was then pressed into tablets, crushed, and sieved to retain 20-40 mesh CoMo / Al2O3 oxidation state catalyst particles for later use.
[0046] (4) Immersing an equal volume of the collected CoMo / Al2O3 oxidized catalyst in an ammonium thiosulfate solution, wherein the molar ratio of S to (Co+Mo) is 3:1, and then drying at 105°C for 8 hours to obtain a presulfided catalyst; (5) The presulfurized catalyst was placed in a 300 mL autoclave and heated at a hydrogen pressure of 30 bar and a heating rate of 3 o C / min, and at 300 o C is maintained for 60 min to carry out reduction to obtain a sulfided residue hydrocracking catalyst.
[0047] Effect Example 1 Catalytic evaluation experiment: A 300 mL high pressure autoclave (Parr Instrument) was used to systematically evaluate the residue oil hydrogenation performance of 300 mg of the catalysts obtained in Examples 1-4 and Comparative Examples 1-2.
[0048] At room temperature, 50 g of model residue oil was added to the autoclave. The composition of the model residue oil was: 3 wt% dibenzothiophene, 2 wt% naphthalene and 0.5 wt% n-nonane in n-heptane. Among them, dibenzothiophene is a representative sulfur compound used to examine the hydrodesulfurization performance of the catalyst, naphthalene is a representative diesel aromatic compound used to examine the hydrogenation performance of the catalyst, and n-nonane is an internal standard for gas chromatography analysis. After nitrogen purging 3 times, the hydrogen pressure was increased to 50 bar, and then the reactor was heated to 350 o C, and react for 4 hours, with a stirring speed of 700 rpm. The product analysis was performed using gas chromatography (GC-FID), the chromatograph was Agilent 7890 model, the chromatographic column was HP-5ms (30 m×0.25 mm×0.25 μm) inert chromatographic column, and helium was used as the carrier gas. The reaction data obtained are shown in Table 1.
[0049] Table 1
[0050] From the above results, it can be seen that the specific surface area of the catalyst prepared by ball milling coupled with Joule heat pulse is 98-135m 2 / g, slightly smaller than the catalyst prepared by traditional impregnation method.
[0051] Hydrodesulfurization reaction of dibenzothiophene: From the data in Table 1, it can be seen that the catalyst prepared by ball milling coupled with Joule heat pulse has good hydrodesulfurization performance, which is better than the catalyst prepared by the traditional impregnation method. Compared with the catalyst containing Ni and Mo, the dehydrogenation and sulfurization conversion rate of the catalyst containing Co and Mo is higher.
[0052] In addition, the activity of the catalyst decreased with increasing the number of Joule heat pulses and temperature, which may be due to the decrease in the specific surface area of the catalyst.
[0053] As for product selectivity, compared with hydrogenation followed by desulfurization, the direct hydrodesulfurization reaction to obtain biphenyl always dominates.
[0054] Hydrogenation reaction of naphthalene: Compared with the catalysts containing Co and Mo, the catalysts containing Ni and Mo have higher naphthalene hydrogenation conversion rates.
[0055] Although the embodiments disclosed in the present invention are as above, the contents described are only embodiments adopted to facilitate understanding of the present invention and are not intended to limit the present invention. Any technician in the field to which the present invention belongs can make any modifications and changes in the form and details of implementation without departing from the spirit and scope disclosed in the present invention, but the patent protection scope of the present invention shall still be subject to the scope defined in the attached claims.
Claims
1. A method for preparing a residue oil hydrocracking catalyst by ball milling coupled with Joule heat pulse, comprising the following steps: (1) Mixing a salt compound containing a metal element X with a salt compound containing Mo, a salt compound containing Al, and a molecular sieve to obtain a precursor material; the metal element X is at least one of Ni and Co; (2) adding the precursor material into a ball mill, adding a grinding solvent and grinding balls for ball milling to obtain a ground material; (3) drying the ground material and subjecting it to Joule heat pulse treatment to obtain catalyst powder; and then tableting, crushing and screening to obtain X-Mo / Al2O3 oxidation state catalyst particles; (4) immersing equal volumes of the X-Mo / Al2O3 oxidation state catalyst particles in an ammonium thiosulfate solution for presulfidation to obtain a presulfided catalyst; (5) Reducing the presulfided catalyst in a hydrogen atmosphere to obtain the residue hydrocracking catalyst in a sulfided state.
2. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: The molar ratio of X metal element, Mo and Al is 1:(1-6):(3-30).
3. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: In step (1), the mass proportion of the molecular sieve in the precursor material is (1-10)%.
4. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: The grinding solvent in step (2) is isopropanol; the volume ratio of isopropanol to the precursor material is (0.5-3):
1.
5. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: In step (2), the diameters of the grinding balls are 20 mm, 10 mm and 5 mm respectively; the ball-to-material ratio is (3-5):1, the ball milling speed is (100-600) r / min, and the ball milling time is (6-12) h.
6. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: In step (3), the method of Joule heat pulse treatment is: replace the air in the sintering box with monatomic gas Ar, set the pulse conditions: heating rate is (2000~4000)℃ / s, the number of pulses is (3~15) times, the upper limit temperature is (600~1000)℃, and the cooling time is ≤1.5s, down to 450℃±10℃.
7. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: In step (4), the ratio of the molar amount of S to the total molar amount of the X metal element and Mo is (2-6):
1.
8. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 7, characterized in that: In step (4), the ratio of the molar amount of S to the total molar amount of the X metal element and Mo is 3:
1.
9. The method for preparing a residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to claim 1, characterized in that: In step (5), the hydrogen pressure is 20-40 bar and the heating rate is 1-5 o C / min, and at 200~350 o C is maintained for 30 to 120 minutes for reduction.
10. A residue hydrocracking catalyst, characterized in that: The catalyst is obtained by the method for preparing residue hydrocracking catalyst by ball milling coupled with Joule heat pulse according to any one of claims 1 to 9.